Sustainable management in companies and green transition consequences based on the Polish energy sector in 2014-2024 - Joanna Toborek- Mazur; Karol Partacz (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Sustainable management in the Polish energy sector in 2014–2024 plays a key role in the transformation process towards the development of green energy. The paper includes a study of the five largest companies in the energy sector in Poland – Enea, Energa, PGE, PGNiG and Tauron – using the Fama-French model to assess the relationship between the excess company rates of return and the excess market rate of return. The results indicate a varied impact of sustainable activities on the financial results and investment risk of companies. The energy transformation in Poland, based on the increase in the share of renewable energy sources is not only an operational challenge, but also an opportunity for long-term development and ESG improvement. The research has shown that the positive consequences of implementing green energy include a reduction in CO₂ emissions and access to new investment funds, while the negative aspects result from the increasing costs of transformation and regulatory pressure. The final conclusions underline the need to implement comprehensive sustainability management strategies to balance the risks and benefits of the green transformation in a dynamically changing market environment.